CircRNA May Not Be “Circular” - Sun, Handong; Wu, Zijuan; Liu, Ming; Yu, Liang; Li, Jianyong; Zhang, Jinwen; Ding, Xiangming; Jin, Hui (Frontiers in Genetics, 2021)
Circular RNA (circRNA) is a novel regulatory non-coding RNA and participates in diverse physiological and pathological processes. However, the structures and molecular mechanisms of circRNAs remain unclear. In this study, taking advantage of openly databases and bioinformatics analysis, we observed lots of internal complementary base-pairing sequences (ICBPS) existed in plenty of circRNAs, especially in extremely long circRNAs (el-circRNAs, > 5,000 nt). The result indicated that circRNA may not be a simple circular structure. In addition, we put forward the hypothesis of "open-close effect " in the transition for specific circRNA from normal state to morbid state. Taken together, our results not only expand the knowledge of circRNAs, but also highlight the potential molecular mechanism of circRNAs.